Scaffolds fabricated via two-photon polymerisation for regulating cell morphology and differentiation - Zheyu Yao; Xiuzhen Zhang; Wenhui Yu; Zhen Xiao; Wenli Zhou; Dongfeng Qi; Wuhong Xin; Weilong Cao; Hongyu Zheng (Virtual and Physical Prototyping)
Three-dimensional (3D) cell culture scaffolds play a key role in guiding cell fate. The fine-tunability of these scaffolds is essential for accurately replicating in vivo conditions and revealing cellular behaviours. In this study, two-photon polymerisation (TPP) technology was employed to create 3D scaffolds with woodpile and honeycomb architectures. The influence of scaffold geometry and pore dimensions on the proliferation, morphology, orientation, and differentiation of human mesenchymal stem cells (hMSCs) was investigated through multi-staining fluorescence and 3D confocal imaging technique. It was revealed that hMSCs cultured within these 3D scaffolds demonstrated higher density up to 15.04 ± 1.46 cells/100 × 100 μm2 after a 6-day culture compared to their 2D counterparts (7.47 ± 1.42 cells/100 × 100 μm2). Furthermore, hMSCs grown on the woodpile scaffolds displayed elongated morphology, with approximately 50% aligning along the columns. In contrast, hMSCs cultivated on honeycomb structures exhibited triangular and crescent cellular shapes, with a random orientation. Notably, compared to the control group, the cells on the scaffolds exhibited smaller nucleus areas, lower circularity, and aspect ratios, but these values increased as pore size increased. Furthermore, ALP staining showed a greater tendency for osteogenic differentiation with larger pore sizes. These TPP-fabricated 3D scaffolds hold immense promise for advancing understanding of cellular behaviour.